14 NNEdPro global centre response to the UK government obesity strategy. (12th April 2022) - McAuliffe, Shane; Vale, Marjorie Lima do; Macaninch, Elaine; Bradfield, James; Crocombe, Dominic; Kargbo, Sento; Rio, Daniele Del; Fallon, Emily; Martyn, Kathy; Kohlmeier, Martin; Beck, Eleanor; Almoosawi, Suzana; et al.
Abstract : Background: Following considerable interest in the relationship between obesity and COVID-19, the UK Government have released a policy paper: 'Tackling obesity: empowering adults and children to live healthier lives'. 1 This response may be focused on a limited and potentially historical view of overweight and obesity. We consider the complexity of the condition, its determinants, and co-existing conditions. 2 Objectives: We sought to gain consensus iteratively, using implementation framework thinking, to advocate for the appreciation of a wider, more complete understanding of the existing science behind obesity and the appropriate strategies needed to address it. Results: We identified four strategic points and provided recommendations for more comprehensive coverage and greater impact: 1 . Improving focus and messaging 2. Understanding drivers of food choice and nutritional status 3 . Promoting healthy eating from early years 4. Addressing the complexity of obesity Discussion: 1. Effective messaging should be inclusive, collaborative and non-judgemental, promoting co-participation in the development of messages used in public national campaigns. 3 2. Higher rates of obesity are observed in socioeconomically deprived groups who rely on food assistance programmes, in which nutritional quality could be improved through involvement of nutrition professionals. 4 In order to influence behaviour, basic food literacy and financial management skills could be developed, while subsidies for healthier alternatives may complement taxes on less healthy foods. 5 3. Advocating for better education on food science and nutrition from early learning sectors will promote increased awareness early in life. 6 This could be augmented by reinstatement of initiatives like the healthy start programme. 4. Human health is multi-dimensional, therefore focussing on a single-metric risks oversimplifying this complexity and undervaluing the importance of healthy behaviours, even those not directly associated with weight. 7 Instead, we should consider positive lifestyle habits, rather than a narrow focus on weight or BMI alone for the individual, informed by existing and accepted scientific findings. Conclusion: An integrated systems approach ought to be developed with a multipronged intervention strategy, targeting food production, supply and environments as well as marketing to improve availability of as well as accessibility to more nutrient-rich but less energy-dense foods. These combined with appropriate food education for consumers would enable more consistently healthy food choices. Acknowledgements: NNEdPro Virtual Core and Global Innovation Panel; Nutrition and COVID19 Taskforce References: UK Government - Tackling obesity: empowering adults and children to live healthier lives. July 2020. Foresight, Obesity Systems Map. 2007. Language Matters: Language and diabetes. 2018. Fallaize R, Newlove J, White A, Lovegrove JA. Nutritional adequacy and content of food bank parcels in Oxfordshire, UK: a comparative analysis of independent and organisational provision. J Hum Nutr Diet 2020;33 :477–486. https://doi.org/10.1111/jhn.12740 Garcia A, Reardon R, Hammond E, Parrett A, Gebbie-Diben A. Evaluation of the 'eat better feel better' cooking programme to tackle barriers to healthy eating. International Journal of Environmental Research and Public Health 2017;14 (4):380. doi:10.3390/ijerph14040380 Oostindjer M, Aschemann-Witzel J, Wang Q, Skuland S, Egelandsdal B, Amdam G, et al . Are school meals a viable and sustainable tool to improve the healthiness and sustainability of children´s diet and food consumption? A cross-national comparative perspective. Critical Reviews In Food 2016. Salas-Salvado J, Bullo M, Babio N, Martinez-Gonzalez M, Ibarrola-Jurado N, Basora J, et al . Reduction in the incidence of type 2 diabetes with the mediterranean diet: results of the PREDIMED-Reus nutrition intervention randomized trial. Diabetes Care 2010;34 (1):14–19. doi:10.2337/dc10-1288